Viable approach to manage superficial enamel discoloration - Naveen Chhabra; Kiran P Singbal (Wolters Kluwer Medknow Publications, 2010)
Esthetics is a primary concern amongst young patients and represents a challenge to the dentist. Discolored teeth are frequently seen in the general population. Several techniques have been devised to minimize or completely eliminate tooth discoloration. This case report highlights the successful management of enamel discoloration via modified microabrasion technique followed by in office bleaching.